"Alternative worlds" - differences in a coverage of events in TVN's "Facts" and TVP's "News" - Seklecka, Aleksandra (Political Preferences, 2017)
A subject of research are television news bulletins (public television – “Wiadomości” and private television – “Fakty”) in view of a presentation of information way. An analyse of a piece of discourse helps show differences between journalists who can present opposite facts, and consequently they can create public opinion. A research focus on a subject touch on news bulletins, different elements which concur to do news and the background. An aim of the analyse is also an explanation of causes differences in reporting on. Key words: TV News Bulletin, reporting on events, relations between media and politics